2014
DOI: 10.1186/1477-9560-12-17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between angiotensin I-converting enzyme insertion/deletion gene polymorphism and retinal vein occlusion

Abstract: To evaluate the association between angiotensin I-converting enzyme insertion/deletion (ACE I/D) gene polymorphism and retinal vein occlusion (RVO). A total of 80 patients with retinal vein occlusion who was admitted to the Eye Department of Kartal Training and Research Hospital between 2008 and 2011, and 80 subjects were enrolled in this retrospective case–control study. Patients who experienced RVO within one week to six months of study enrolment were included, and those with coronary artery diseases, prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The ACE gene DD genotype is thought to be associated with an increased risk of rheumatic heart disease in the Saudi population (Al-Harbi et al, 2015), with nitric oxide metabolite levels and systolic blood pressure in clinically healthy Mexican men (no effect in women) (Avila-Vanzzini et al, 2015), with high altitude pulmonary edema in an Indian population (Bhagi et al, 2015), with sepsis susceptibility in Chinese patients (Yang and Zhou, 2015), with periodontal disease susceptibility in a Korean population (Kang et al, 2015), and with cancer risk in Caucasians (Zhang et al, 2014). It has been suggested that ACE gene I/D polymorphism is a genetic risk factor for Alzheimer's disease in a Chinese population (Yuan et al, 2015), while there is reportedly no association between ACE I/D gene polymorphism and a number of conditions and associated risks including type 1 diabetic nephropathy (T1DN) susceptibility and the risk of patients with type 1 diabetes mellitus developing T1DN in a Caucasian population , chronic obstructive pulmonary disease (Ayada et al, 2014) and retinal vein occlusion (Kutlutürk et al, 2014) in a Turkish population, as well as type 2 diabetic nephropathy (T2DN) susceptibility and the risk of patients with type 2 diabetes mellitus developing T2DN in Caucasian populations . In a meta-analysis by Song and Lee (2014), no association was observed between ACE gene I/D polymorphism and the susceptibility to systemic sclerosis in four European studies and one study each in Asian, African American, and Latin American populations comprising a total of 837 cases and 754 controls.…”
Section: Discussionmentioning
confidence: 99%
“…The ACE gene DD genotype is thought to be associated with an increased risk of rheumatic heart disease in the Saudi population (Al-Harbi et al, 2015), with nitric oxide metabolite levels and systolic blood pressure in clinically healthy Mexican men (no effect in women) (Avila-Vanzzini et al, 2015), with high altitude pulmonary edema in an Indian population (Bhagi et al, 2015), with sepsis susceptibility in Chinese patients (Yang and Zhou, 2015), with periodontal disease susceptibility in a Korean population (Kang et al, 2015), and with cancer risk in Caucasians (Zhang et al, 2014). It has been suggested that ACE gene I/D polymorphism is a genetic risk factor for Alzheimer's disease in a Chinese population (Yuan et al, 2015), while there is reportedly no association between ACE I/D gene polymorphism and a number of conditions and associated risks including type 1 diabetic nephropathy (T1DN) susceptibility and the risk of patients with type 1 diabetes mellitus developing T1DN in a Caucasian population , chronic obstructive pulmonary disease (Ayada et al, 2014) and retinal vein occlusion (Kutlutürk et al, 2014) in a Turkish population, as well as type 2 diabetic nephropathy (T2DN) susceptibility and the risk of patients with type 2 diabetes mellitus developing T2DN in Caucasian populations . In a meta-analysis by Song and Lee (2014), no association was observed between ACE gene I/D polymorphism and the susceptibility to systemic sclerosis in four European studies and one study each in Asian, African American, and Latin American populations comprising a total of 837 cases and 754 controls.…”
Section: Discussionmentioning
confidence: 99%
“…Some other researchers aimed to evaluate the association of atherosclerosis-related genetic polymorphisms including angiotensin II type 1 receptor (AGTR1) A1166C, angiotensin I–converting enzyme (ACE) insertion/deletion, platelet glycoprotein Ia/IIa (GpIa/IIa) C807T/G873A, matrix metalloproteinase 2 (MMP2) 1306C/T, tissue inhibitors of matrix metalloproteinase 2 (TIMP2) G418C and adiponectin +276 G/T with RVO [ 36 , 37 , 38 , 39 , 40 , 41 ]. Both Demir et al [ 41 ] and Christodoulou et al [ 36 ] suggested that adiponectin +276 T allele carriers and AGTR1 C allele carriers are likely to be at increased risk for RVO.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II also elevates PAI-1 levels, which results in a decrease in fibrinolytic activity. Previous studies have shown that the plasma level of angiotensin II is closely associated with ACE gene polymorphisms [ 46 , 47 ]. ACE I/D gene polymorphism has been described as an independent risk factor for thrombotic diseases [ 24 ].…”
Section: Thrombophiliamentioning
confidence: 99%